2021
DOI: 10.31635/ccschem.020.202000238
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Strategy for Precise Fabrication of Rigid–Flexible Coupling Dendrimers toward Self-Coordinated Hierarchical Assembly

Abstract: Advances in nanotechnology depend upon expanding the ability to create biologically inspired complex materials with well-defined multidimensional structures. Fabrication of hybrid hierarchical structures by combining colloidal organic and inorganic building blocks remains a challenge due to the difficulty in preparing a diverse spectrum of rigid-flexible coupling units of precise shape and size. Herewe report a general strategy for crafting a myriad of uniform aggregates via manipulating self-assembly of disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Schematic representation of 1→7 divergent approach to precisely tailor rigid‐flexibly coupling POSS dendrimers with well‐defined geometry and customized self‐assembly. [ 96 ] …”
Section: Molecular Design Of Poss‐based Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of 1→7 divergent approach to precisely tailor rigid‐flexibly coupling POSS dendrimers with well‐defined geometry and customized self‐assembly. [ 96 ] …”
Section: Molecular Design Of Poss‐based Hybrid Materialsmentioning
confidence: 99%
“…modular nanofabrication of well‐organized dendritic polymers towards artificial functional systems with the intriguing properties for the advanced biological applications. [ 96 ]…”
Section: Molecular Design Of Poss‐based Hybrid Materialsmentioning
confidence: 99%
“…On the one hand, physical crosslinkers mainly include the hydrophobic-hydrophobic, host-guest, ionic or electrostatic, crystallization and stereo complex interactions, which can cause the formation of polymer network in mild conditions ( Hoffman, 2012 ; Sivashanmugam et al, 2015 ; Fan et al, 2019 ; Zhu C.X. et al, 2019 ; Wang et al, 2020a ). Physically crosslinked hydrogels possess great advantages in biological applications because of the absence of chemical crosslinkers that may bring about the unpredictable and potential toxicity for the tissues, but their reversible architectures, poor stability and low mechanics greatly limited the scope of applications ( Zhang et al, 2013 ; Maitra and Shukla, 2014 ; Parhi, 2017 ; Li et al, 2018 ).…”
Section: Cs-based Hydrogelsmentioning
confidence: 99%
“…Wang et al [ 153 ] reported a combined experiment–simulation co-study detailing a general strategy to construct uniform aggregates by manipulating self-assembly of dendrimers with precisely controlled polyhedral oligomeric silsesquioxane (POSS)-embedded cores. The authors created different types of amphiphilic dendrimers with rigid–flexible coupling POSS-embedded cores, different PEG chain lengths, and various geometries.…”
Section: Polymer-based Smart Nanocarriersmentioning
confidence: 99%
“… ( a ) Schematic of self-assembly of nanoarchitectures from Janus dendrimers and the corresponding structure–concentration phase diagram for amphiphilic dendrimer aqueous solutions [ 150 ]. ( b ) Self-assembled morphologies by various C a -POSS b -PEG c polymers observed by microscopy ( top , with zoom-in on nanoscopic feature in the middle panel) and corresponding DPD modelling images of self-assemblies by the amphiphilic polymers at the initial polymer concentration of 1 mg/mL in aqueous solutions ( bottom ) [ 153 ]. ( c ) Typical calculated states of the interactions between a lipid bilayer membrane and a PAMAM dendrimer conjugated with ligands.…”
Section: Figurementioning
confidence: 99%